Evaluation of Biodegradable Fixation Application for Jaw Fracture in Pediatric Patients - Prasetya, Denta Aditya; Widiastuti, Maria Goreti; Hasan, Cahya Yustisia (Odonto : Dental Journal, 2023)
Background: The treatment of jaw fractures in pediatric patients need a special concern and different management than adult patients due to their dynamic and structural changes following their growth patterns. Treatment by open reduction and internal fixation (ORIF) using titanium or biodegradable plates as osteosynthesis material is indicated for displaced jaw fracture. Biodegradable fixation could be used as an alternative choice, using plates and screw that will decompose along with bone healing. Case: Two pediatric patients brought to RSUP Dr. Sardjito, Yogyakarta with complaints of jawbone fracture. The first patient was a 7-years-old woman diagnosed with mandibular symphysis fracture and a left mandibular kondilus fracture, while the second patient was a 15-years-old woman diagnosed with malunion of left maxillary fracture. Fracture treatment was performed using biodegradable fixation. The first patient was repositioned according to the anatomical state and the second patient the maxillary refracture was done before repositioning. Patients were evaluated clinically for up to three months postoperatively and radiological imaging was performed. Evaluation results show good jaw bone union, no malocclusion, no tooth mobility and no paresthesia in both patients. Intraoral wound dehiscence with exposed plate was found in the second patient at the vestibule of the left uper canine until premolar region and can be resolved by removal of the plates under local anesthesiaConclusions:. Biodegradable as an ideal osteosynthesis material for jaw fracture in pediatric patients